Seroprevalencia del Virus Linfotropico Humano (HTLV I/II) en donantes de sangre del Hospital Regional de Ayacucho entre los años 2015 al 2018 - Aquino Janampa, Maria Magda (2020)
The objective of this research work was to determine the prevalence of serum HTLV type I / II virus obtained from donor applicants from the Blood Bank of the Regional Hospital of Ayacucho from 2015 to 2018. The study sample consisted of 9,876 (100%) screened applicants who were tested for chemiluminescence for HTLV type I / II virus. The data were collected from the log books made in the years 2015 to 2018. The results are annulled through statistical tables of prevalence. The results found show that there was a prevalence of 0.83% (82) of the HTLV virus type I / II, the highest prevalence occurred in 2015 with 1.37% (27) of a total of 1,973 screened applicants. According to sex, the highest prevalence is in the male sex with 0.52% (51), as for the ages, the highest prevalence occurred in donors aged 20 to 29 years with a prevalence of 0.30% (30). Finally, according to the origin, the highest prevalence occurs in screened applicants from Huamanga with 0.46% (45) cases.